Bioinformatic Analyses of Renal Ischaemia-Reperfusion Injury Models: Identification of Key Genes Involved in the Development of Kidney Disease - Kai Zhu; Ting Zheng; Xinghua Chen; Huiming Wang (Karger Publishers, 2018)
Background/Aims: To develop a novel strategy for the treatment of kidney disease, we explored potential molecular targets involved in the development of renal ischaemia-reperfusion injury (IRI). Methods: The Gene expression profile data of GSE27274, including controls and rats subjected to renal IRI and reperfusion for 24 h (IR24) or 120 h (IR120), was obtained from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were analysed using the limma package. Gene Ontology (GO) and pathway functional enrichment analyses of common DEGs were carried out. Protein-protein interactions (PPI) and miRNA-DEG network analyses were performed using the STRING database and WebGestalt, respectively, followed by network construction using Cytoscape. Results: In total, 80 common DEGs (41 up- and 39 downregulated genes) between IR24 and IR120 were screened. Genes encoding tissue inhibitor of matrix metalloproteinase-1 (Timp1), secreted phosphoprotein 1 (Spp1) and dimethylglycine dehydrogenase (Dmgdh) were identified as hub genes in the PPI network and may be significant in the development of renal IRI. Upregulated Spp1 was enriched in the inflammatory response, and downregulated Dmgdh was enriched in the catabolic process of the amino acid betaine. In reactome pathway analyses, Spp1 was enriched in toll-like receptor signalling, and Dmgdh was enriched in glycine, serine and threonine metabolic pathways. The common DEGs were mainly regulated by 15 miRNA clusters. Conclusion: Timp1, Spp1, Dmgdh, miR-142-5p and miR-181a may be potential targets or biomarkers for the development of renal IRI.